LISAT PLATELET DAN MEDIUM TERKONDISI SEL PUNCA MESENSIMAL UNTUK MEMPERBAIKI KULIT MENUA DINI Kajian In-vitro pada Fibroblas Kulit Manusia Menua Dini Buatan - , Yohanes Widodo, dr., Sp.KK(K), Prof. Dr. dr. Hardyanto Soebono, Sp.KK(K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Solar radiation onto human skin, mainly ultraviolet A (UVA), can stimulate premature aging skin because of its effects on human dermal fibroblasts (proliferations, collagen depositions, migrations, and TGF-Î² consumptions). A number of evidence demonstrate that Various biological materials such as platelet lysates (PL), Whartonâs Jelly Stem Cells Conditioned Media (WJ) and Adipose Derived Stem Cells Conditioned Media (AD), may improve healing process in chronic ulcers Objectives: This study was performed to evaluate potency of various concentration of PL, WJ, and AD in improving skin aging of human dermal fibroblasts. Methods: A quasi experimental design was done in artificially aged human dermal fibroblasts. Fibroblast cultivated more than 3 passages (11-13 years olds boyâs foreskins were divided into two groups: Group I consisted of 10 kJ/cm2 UVA induced aged fibroblasts and Group II were normal fibroblasts without UVA irradiation as positive control. Group I were divided into 4 subgroups: subgroup 1â3 were treated by various concentration of PL, WJ, AD consecutively and subgroup 4 was a negative control. They were cultured in DMEM standard media. After treatments, they were evaluated its proliferations, migrations, collagen depositions, and level of extracellular TGF-Î². Fibroblast proliferation, migration, deposition was measured by using MTT assay, Scratch assay, Insoluble Sirius Red collagen assay, respectively, while the level of TGF- was tested by using ELISA. Results: Cultivation of aged fibroblasts in 50% PL showed significant (P<0.05) elevation of proliferations, migrations, and collagen depositions compared to negative control, but they did not have reduction of extracellulary TGF-Î² levels significantly (p>0.05). Cultivation of aged fibroblasts in 25% PL showed elevation of extracellulary TGF-Î² levels significantly (p<0.05). Proliferations, migrations, and collagen depositions of aging fibroblast culture in 50% PL were: 0.87Â±0.049 OD